2015
DOI: 10.1126/scisignal.aaa8859
|View full text |Cite
|
Sign up to set email alerts
|

ERK reinforces actin polymerization to power persistent edge protrusion during motility

Abstract: Cells move through perpetual protrusion and retraction cycles at the leading edge. These cycles are coordinated with substrate adhesion and retraction of the cell rear. Here, we tracked spatial and temporal fluctuations in the molecular activities of individual moving cells to elucidate how extracellular regulated kinase (ERK) signaling controlled the dynamics of protrusion and retraction cycles. ERK is activated by many cell-surface receptors and we found that ERK signaling specifically reinforced cellular pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
88
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(97 citation statements)
references
References 58 publications
9
88
0
Order By: Relevance
“…Detection of directional cues may be an important function of the EGFR signaling network. EGF gradient sensing or ERK heterogeneities have been implicated in mechanotransduction, cell polarization, and motility121314.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Detection of directional cues may be an important function of the EGFR signaling network. EGF gradient sensing or ERK heterogeneities have been implicated in mechanotransduction, cell polarization, and motility121314.…”
Section: Resultsmentioning
confidence: 99%
“…Unsurprisingly, dysregulated MAPK signaling underlies many cancers5. There is growing evidence that the cell fate decisions are regulated by temporal678 or even spatiotemporal profiles of ERK and RAF9101112131415. It is thus important to understand how information about the level and gradient of an extracellular stimulus is encoded and transmitted to intracellular downstream effectors.…”
mentioning
confidence: 99%
“…Our previous work on protrusion mechanics indicated that the growth of branched actin networks primarily serves the reinforcement after protrusion onset of actin assembly against mounting membrane tension (21,27). Therefore, we expected that the canonical nucleator of branched network formation, Arp2/3, would be recruited after protrusion onset and primarily after ezrin depletion.…”
mentioning
confidence: 95%
“…The regulation of this highly dynamic and adaptable mechanism of motion dictates the outcomes of many cellular processes. For example, the stiffness of the branched actin network , the frequency of its oscillations (Mendoza et al, 2015), the relative ratio of elongation and branching (Bisi et al, 2013), and membrane trafficking (Gautier et al, 2011) can be tuned to yield distinct phenotypic effects. This regulation is achieved through a complex coordination of many signaling pathways in which RhoGTPases, small molecular switches that integrate multiple inputs to orchestrate the dynamics of the cytoskeleton, play a pivotal role.…”
Section: Introductionmentioning
confidence: 99%